2011
DOI: 10.1098/rsta.2011.0238
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal properties of cortical haemodynamic response to auditory stimuli in sleeping infants revealed by multi-channel near-infrared spectroscopy

Abstract: Multi-channel near-infrared spectroscopy (NIRS) has been used as a neuroimaging tool to study functional activation of the developing brain in infants. In this paper, we focus on spatiotemporal dynamics of cortical oxygenation changes during sensory processing in young infants. We use a 94-channel NIRS system to assess the activity of wide regions of the cortex in quietly sleeping three-month-old infants. Auditory stimuli composed of a random sequence of pure tones induced haemodynamic changes not only in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 79 publications
2
26
0
Order By: Relevance
“…When periodically presented, the auditory stimulation generates, in the temporal regions, cortical activity that is spread to neighboring regions, generating spontaneous activity. These results demonstrate the existence of short distance cortical connectivity in these regions 24 .…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…When periodically presented, the auditory stimulation generates, in the temporal regions, cortical activity that is spread to neighboring regions, generating spontaneous activity. These results demonstrate the existence of short distance cortical connectivity in these regions 24 .…”
Section: Discussionsupporting
confidence: 51%
“…The results of this group were consistent as they reported that the right and left auditory cortex are equally sensitive to rapid acoustic modulations, while the slow ones are preferably processed by the right auditory cortex 21,22 . It was observed an increase in the oxyhemoglobin rates and hemodynamic responses not only in bilateral temporal auditory regions, but also in the occipital and prefrontal regions due to stimulation with pure tones 24 in addition to the temporoparietal region due to different sequence of tones 23 .…”
Section: Figura 2 Principais Características Dos Artigos Selecionadomentioning
confidence: 99%
See 1 more Smart Citation
“…However, a number of findings suggest that this widespread activation is a developmentally relevant phenomenon. First, fNIRS paradigms, even with high-density arrays (e.g., 94 channels), have revealed widespread patterns of activation in occipital, occipitotemporal, and frontal areas in infants between birth and 3 months of age, for both simple visual and auditory stimuli (Taga et al 2003, 2011; Watanabe et al 2008, 2010). Second, in preterm infants, activation in the occipital cortex is less robust, and at times absent (Lee et al 2012), and the extent of activation increases with age in visual (Born et al 2000) and even somatosensory studies [unilateral activation in preterm infants versus bilateral activation in term infants (Arichi et al 2012)].…”
Section: Domain-specific Findings About Infant Cognitionmentioning
confidence: 99%
“…The most significant explosion of interest in this field has been in studies of neurodevelopment. Despite the difficulties of making measurements in (semi-mobile) young infants, this remains one of the most promising applications of NIRS technology because it satisfies an unmet need; neuroimaging in infants is difficult with other modalities, and optical techniques which can provide data on functional activation, connectivity and resting state can be used to literally watch the brain develop [25]. The challenges of reducing attrition rates particularly in studies of awake infants were discussed.…”
Section: (I) Measurement Of Haemodynamic Response To Neuronal Activationmentioning
confidence: 99%